RNA-seq analysis reveals TRPC genes to impact an unexpected number of metabolic and regulatory pathways - Formoso, Karina (2020)
Fil: Formoso, Karina. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Biología Celular y Molecular; Argentina